Effect of Stanozolol on Factors VIII and IX and Serum Aminotransferases in Haemophilia - Greer, I A; Greaves, M; Madhok, R; McLoughlin, K; Porter, N; Lowe, G D O; Preston, F E; Forbes, C D (Thrombosis and Haemostasis, 1985)
The treatment of haemophilia has been dramatically improved since the introduction of factor VIII and IX concentrates, however these concentrates have brought new problems such as hepatitis and A.I.D.S. An oral agent which could raise endogenous levels of factor VIII and IX would be of great benefit. Danazol, an anabolic steroid, has recently been shown to increase levels of factors VIII and IX in haemophilia. We therefore studied the effect of stanozolol, a closely related anabolic steroid, in 15 patients with haemophilia A or Christmas disease over a 2-4 week period. There was no consistent change in factor VIIIc or factor IX, and fibrinolysis was significantly enhanced. No effect was apparent on the incidence of spontaneous bleeds. However serum aminotransferases which were abnormal in 11 of the 15 patients at the start of the study fell significantly with stanozolol therapy. This raises the interesting possibility that anabolic steroids may be beneficial in patients with chronic liver diseases.
Keywords: Stanozolol; Haemophilia; Fibrinolysis; Serum aminotransferases